Valorization of fish from the Adriatic Sea: nutritional properties and shelf life prolongation of Aphia minuta through essential oils - Marino, Rosaria; Albenzio, Marzia; della Malva, Antonella; Racioppo, Angela; Speranza, Barbara; Bevilacqua, Antonio (Frontiers in Nutrition, 2024)
This study aimed to exploit the nutritional and microbiological qualities of Aphia minuta, which are still largely unknown; they are collected from Golfo di Manfredonia (Adriatic Sea). Chemical composition, fatty acids, and amino acid profiles were evaluated during winter, spring, and summer (two samples each season). The protein content was highest in spring, while no significant differences were found for fat and ash contents across all sampling periods. Fatty acid profile analyses revealed that monounsaturated and polyunsaturated fatty acids were affected by the sampling season. Notably, the value of n-3 polyunsaturated fatty acids increased in spring and summer compared to the winter season. The highest content of essential amino acids was measured during the spring and summer seasons (P < 0.01), with leucine and lysine being the most dominant. Regardless of the fishing season, from a nutritional point of view, this species is an excellent source of bioactive compounds. This study also focused on the microbiological quality and shelf life of Aphia minuta. Initially, the bioactivity of three different essential oils (thymol, lemon, and citrus extract) was tested on Pseudomonas fluorescens, Staphylococcus aureus, and Escherichia coli. These essential oils were then combined with various packaging materials (conventional, maize starch, and polylactate) and packaging atmosphere (air, vacuum, and a modified atmosphere with reduced oxygen content). The results indicated that combining citrus extract with vacuum packaging significantly reduced the psychrotrophic viable count to undetectable levels after 7 days. This study suggests some important considerations for exploiting and expanding the market of the Aphia minuta.